1982
DOI: 10.1113/jphysiol.1982.sp014126
|View full text |Cite
|
Sign up to set email alerts
|

The formation of appropriate central and peripheral connexions by foreign sensory neurones of the bullfrog

Abstract: SUMMARY1. The ability of foreign sensory neurones to form novel reflex pathways was studied in bullfrogs by removing, during early larval stages of development, the dorsal root ganglion (d.r.g. 2) that normally provides the entire sensory innervation of the front limb.2. After the operation these tadpoles metamorphosed into frogs that responded to sensory stimuli and had nearly normal use of the limb. Sensation in the limb was mediated by sensory neurones located in an adjacent ganglion (d.r.g. 3); these neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 14 publications
3
25
0
Order By: Relevance
“…For example, if thoracic DRG, which normally lack any muscle spindle afferents, are forced to supply forelimb muscles, these ganglia will produce muscle spindle afferents that project to the appropriate forelimb motoneurons (Frank and Westerfield, 1982;Smith and Frank, 1987). These results indicate that some signal(s) from peripheral targets can determine both the general identity of sensory neurons (i.e., the muscle spindle afferent phenotype) and their specific identity in terms of which motoneurons they choose as synaptic partners.…”
Section: Abstract: Neurotrophins; Sensory Neurons; Muscle Spindle Afmentioning
confidence: 78%
See 1 more Smart Citation
“…For example, if thoracic DRG, which normally lack any muscle spindle afferents, are forced to supply forelimb muscles, these ganglia will produce muscle spindle afferents that project to the appropriate forelimb motoneurons (Frank and Westerfield, 1982;Smith and Frank, 1987). These results indicate that some signal(s) from peripheral targets can determine both the general identity of sensory neurons (i.e., the muscle spindle afferent phenotype) and their specific identity in terms of which motoneurons they choose as synaptic partners.…”
Section: Abstract: Neurotrophins; Sensory Neurons; Muscle Spindle Afmentioning
confidence: 78%
“…These studies showed that limb muscle could promote the development of muscle spindle afferents in thoracic DRG, which do not normally produce neurons of this phenotype. Moreover, these neurons made connections with motoneurons that were appropriate for the specific muscle that was supplied (Frank and Westerfield, 1982;Smith and Frank, 1987). Thus, signals from limb muscle can determine both the general phenotype of sensory neurons (i.e., muscle spindle afferent) and which motoneurons they will choose as synaptic partners.…”
Section: Nt3 and The Specification Of Muscle Spindle Afferentsmentioning
confidence: 99%
“…When embryonic amphibian sensory afferents were redirected, their central projections were appropriate for the new target (Frank and Westerfield, 1982;Frank, 1987, 1988). Rerouting of sensory afferents from muscle to skin alters Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, minor changes in the central connections of the adult mammalian central nervous system have been observed to result from changes in motoneurone innervation (Eccles, Eccles & Magni, 1960;Eccles, Eccles, Shealy & Willis, 1962;Mendell & Scott, 1975;Tsukahara & Fujita, 1976). Frank & Westerfield (1982) have suggested that bull-frog sensory ganglion neurones forced to project to regionally inappropriate targets may be respecified to make functionally appropriate monosynaptic connections with motoneurones that they would normally not innervate (see also Hollyday & Mendell, 1975). In the chick embryo, spinal ganglia neurones do not innervate limb regions or motoneurones left uninnervated by removal of neural crest cells (Eide, Jansen & Ribchester, 1982) or small segments of the neural tube (Honig, 1979).…”
Section: Discussionmentioning
confidence: 99%